FAKTOR KETERLAMBATAN PADA PEMBANGUNAN PROYEK RUMAH SAKIT MUHAMMADIYAH GRESIK - Azlansyah, Moh (Universitas Negeri Surabaya, 2023)
A construction project is a series of works related to development and there is often a discrepancy between planning and implementation which results in delays in construction. The more complex the project, the greater the project will experience development delays, one of which is Muhammadiyah Gresik Hospital. This study used the method of distributing questionnaires directly to respondents related to hospital construction, such as site managers, quality control, implementers, and workers. The results of the questionnaire will be analyzed for validity, reliability and ranking analysis. Based on the results of the ranking analysis, the factor that has the most influence on delays in the construction of the Muhammadiyah Gresik Hospital project is design document errors and the factor that has the least effect is hot weather. Development projects must be planned in as much detail as possible in order to avoid mistakes that can result in project delays.